Does Parental Absence Harm Children's Education? Evidence from Vietnam - Cuong Viet Nguyen; Linh Hoang Vu (Global Labor Organization (GLO), 2022)
This study uses a large-scale dataset from Vietnam to analyze the impacts of parental absence due to migration, death, or divorce on children's school enrollment, for children aged from 7 to 22. We find children from two-parent families have a better chance of enrolling at all levels of education than those from single-parent families. Within single-family types, the negative effect on children of parental divorce is higher than that of parental death, while the effect of parental migration is the lowest. Comparing the effect of single-father and single-mother households, we find that children living with a single mother tend to have higher school enrollment than those living with a single father, indicating the critical role of mothers in children's education.
Keywords: I1; I2; O1; 330; Children; Young; Education; Vietnam